Designing Teaching Activity - Muhammad Rizal Akbar Zamzami; Muhammad Ana Zamzami (Pioneer: Journal of Language and Literature, 2023)
The article discusses the idea of designing teaching approach by using cartoon videos as a tool for teaching vocabulary to young learners, specifically 4th and 5th grade elementary school students who are typically 10-11 years old. The article emphasizes that in the current modern era, a variety of media have already become a part of our daily lives, particularly for children who watch YouTube, Tiktok, and other ssocial media videos. Consequently, teaching and learning process should adapt with the advancement of technology. Designing teaching vocabulary for young learners by using cartoon videos are suitable since young learners are more open-minded, have developed concrete operational thinking, and are motivated to solve their own learning problems. This article also provides a lesson plan which can be utilized in Classroom Action Research (CAR). Overall, the article believes that using cartoon videos is an effective teaching strategy for young learners because it is engaging, enjoyable, and it helps students to learn more effectively.